Determinants of Lack of Physical Activity in Students in Yogyakarta: Determinants of Lack of Physical Activity in Students in Yogyakarta - Octania, Salsabila Dita; Indriani, Indriani; Ningrum, Tyas Sari Ratna (FISIO MU: Physiotherapy Evidences, 2024)
Introduction: Lack of physical activity can increase the risk of health problems such as non-communicable diseases (NCDs); hypertension, Diabetes Mellitus (DM), Stroke, and several types of cancer and has benefits in preventing obesity, improving fitness and mental health. Various constraining factors affecting participation in physical activity such as lack of time, lack of facilities, lack of interest and energy have led to a significant decline in physical activity among university students. The purpose of this study was to identify physical activity and its constraints on university students. Methods: The research method used a cross- sectional approach with a cluster sampling technique. The sample in this study was 120 respondents and data analysis using Spearman's Rank correlation analysis test. The research instrument used questionnaires, namely the Global Physical Activity Questionnaire (GPAQ) and the Barriers to Being Active Quiz (BBAQ). Results: The results showed that physical activity in students was in the low category of as many as 35 respondents (29.2%) with an average MET ± SD of 244.80 ± 209.609 per minute per week and the Spearman's Rank analysis test showed a p-value = 0.017 (<0.005) which means there is a significant relationship between obstacles and physical activity in students. Conclusion: Physical activity in students is still low and not by WHO recommendation standards so university efforts are needed to become a place for the development of health literacy as well as socialization and improvement of healthy behaviour of the academic community to become an active and healthy campus.